Pedagogical Aspects of Riddles: A Critical Examination of Abagusii Riddles - Gachanja, Muigai Wa; Kebaya, Charles (International Journal of Humanities and Social Science, 2013)
This paper is based on a critical examination of pedagogical aspects of riddles among the Abagusii community and opines that riddles play an important role in the education system of notonlychildren but also in adults. Focusing on riddles from the Abagusii communityand while contending that riddles have variousfunctions to play in society such as cultural, social and historical, thestudy interrogates pedagogical valuesembedded inriddles. Primary data for analysis was obtained from a field study conducted among children and adults purposively sampled from the Abagusii community. Theresearchers engaged participatory and observationalapproaches in data collection. Anchored in deconstruction theoryas its theoretical framework, the paper explores various education values and skills inherent in the riddles and shows that both the riddling process and the riddles embody educational values. In this regard, the authors emphasize that riddles should be embraced as an important teaching and instructional method. It is for this reason that the two writers conclude that participating in riddling is not a futile exercise but an educative one based on the pedagogical empowerment in riddles and the riddling process.The study proffers new ways of studying riddles and how they can be utilized in teaching and learning processes in Kenyan schools for integration purposes.
Keywords: Pedagogy; Riddles; Pedagogical empowerment; Education system; Teaching and Learning